Prevalence and heritability of distichiasis in the English Cocker spaniel - Petersen, Tanja (Canine Genet Epidemiol, 2015)
BACKGROUND: Canine distichiasis is a well-known cause of ocular irritation and excessive lacrimation (secretion of tears) in the dog. The term distichiasis originates from the Greek words di and stichos meaning two and rows, respectively, and as the name implies, the condition is characterized by an additional row of cilia, which erupts on the eyelid margin. Many purebred dogs are known to be predisposed to the condition, with many affected individuals within the populations. Even though the problem is widespread, the exact mode of inheritance and the heredity has not been studied extensively. However, some degree of genetic influence has been assumed, due to the high incidences within specific breeds. In the present study we have examined a cohort of English Cocker spaniels in Denmark to determine the prevalence and heritability of the disease. RESULTS: Data from English Cocker spaniels with an ECVO eye examination registered between 2004–2013 were included in the study. The number of dogs examined during this period was 799, and the prevalence of distichiasis within this cohort was estimated at 49.31 % with a gender predisposition that females are more likely to get distichiasis than males. The correlation between the distichiasis status of the parents and their offspring revealed a significant association between the breeding combination of the parents and the occurrence of distichiasis in the offspring (p <0.0001). A relative risk (RR) ranging from 1.3 to 1.8 demonstrates that offspring of two affected parents are more likely to be affected than offspring descending from either one or two unaffected parents. The heritability was estimated to be moderate to high, i.e., 0.22 to 0.51. CONCLUSIONS: The prevalence of distichiasis in English Cocker spaniels from Denmark, examined in 2004–2013 was shown to be extremely high. The relative risk of developing the disease was 1.3 and 1.8 for offspring of one or two affected parents respectively. This together with the moderate to high heritability of the condition indicates that selective breeding could be used to reduce the incidence of distichiasis.